Coral bleaching from a nutrient perspective is understudied: A bibliometric survey - Li, Tangcheng; Huang, Jiahong; Du, Hong; Liu, Xiaojuan; Zhong, Chongming; Lin, Senjie (Frontiers in Marine Science, 2022)
How coral-Symbiodiniaceae mutualistic symbiosis is established, maintained, and disrupted is arguably the most fundamental and central area of coral research. The breakdown of this symbiosis, and consequent coral bleaching, have been frequently attributed to thermal stress, although microbial attack and pollution have also been blamed. Despite the perceived diverse and broad research, it is unclear whether all the potential causes have been given adequate attention and whether some important areas have been overlooked. This work aims to comprehensively review the literature on coral and Symbiodiniaceae research and provide a portrait of the current coral research landscape, hence identifying areas that require more research effort. Data of publication output was extracted from the Web of Science (WoS) from 1986 to 2022 by using the keywords “coral” and “Symbiodiniaceae.” 43,089 and 3,191 papers in the coral and Symbiodiniaceae were identified, most published after 2002. The journal Coral reefs was ranked first regarding the total number of publications on coral or Symbiodiniaceae. The USA, Australia, and China were the top three countries in the number of publications. The network co-occurrence analysis of all keywords in coral and Symbiodiniaceae using VOSviewer showed that biodiversity, climate change, nutrient and survival were the central research area in coral and Symbiodiniaceae. Among them, climate change was the most invested research field, as revealed by the high proportion of published literature, while nutrient was the most understudied area. Thematic evolution analysis revealed that nutrient enrichment combined with elevated temperature was an emerging research field about coral and Symbiodiniaceae. Besides, nitrogen is currently the most studied nutrient. The findings from this study shed light on the trends of coral and Symbiodiniaceae research in the past 36 years, current research hotspots in the field, and areas that need more research investment going forward.